Effect of composite layers on partially wrapped Al-glass/epoxy hybrid tube subjected to axial load - Abbas, T. (American Institute of Physics Inc., 2017)
In this paper effect of composite layers on energy absorption capability of aluminium tube partially wrapped with glass/epoxy has been studied. The samples were manufactured using round aluminium tubes and glass/epoxy. The filament winding method was used to partially wrap aluminium tubes externally with glass/epoxy. The fiber orientation in the partial wrapping of aluminium tubes was 10°. Three different types of composite layers; 4, 6 and 8 were used. The percentage area of aluminium tubes covered by composite layers was 70 , 50 and 30 for 4, 6 and 8 layers, respectively. These samples were tested using a universal testing machine with 5mm/min speed. The results indicate that hybrid tube manufactured by using 8 composite layers has 11.85 and 15.92 more energy absorption as compared to other samples prepared by using 4 and 6 composite layers, respectively. Moreover, mode of failures for these tubes have been discussed in detail. © 2017 Author(s).